Pengaruh Beban Kerja dan Worklife Balance Terhadap Turnover Intention dengan Stres Kerja Sebagai Variabel Intervening pada PT Kridha Multiniaga Prima Cabang Juwana Pati - Siti Aisah; Mochamad Edris; Ag Sunarno H (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the effect of workload and work-life balance on turnover intention with work stress as an intervening variable. The data of this study used primary data in the form of questionnaires. The sampling method used purposive sampling and obtained a sample of 132 respondents. The data analysis used in this study was the structural equation model. The results of this study stated that workload and work-life balance had a positive and significant effect on work stress, work stress had a positive and significant effect on turnover intention, while workload and work-life balance did not have a significant effect on turnover intention.